KARAKTERISTIK ERGONOMIS RANCANG BANGUN WHEELBARROW - Mia Monasari; Rika Ampuh Hadiguna (Institute of Research and Community Outreach - Petra Christian University, 2006)
A Wheelbarrow is one of manual material handling equipments%2C which often used by many people. From survey%2C there are some problems faced by users%2C e.g.%2C high energy expenditure and risk of injuries. To avoid those particular risks in using a wheelbarrow%2C analysis of factors that affect this energy expenditure and risk of injuries will be needed. An experiment based on Taguchi method has been conducted to achieve the optimum combination of factors that increase energy expenditure rate and decrease the energy expenditure variance. The analysis of body posture shows that the best posture in using a wheelbarrow is when the straight arm in line with vertebrae. The analysis of subjective complaints shos that palm of hands%2C arms%2C shoulders%2C elbows and wrists are the most possible parts of body having risk injuries. Based on these information and analysis%2C a good wheelbarrow is a wheelbarrow that has the distance of man support and wheel axis smaller than 110 cm. The propose design of a new wheelbarrow has these following properties. The horizontal distance beetween weight point an wheel axis is smaller than 26.53 cm%2C the vertical distance beetween weight point and wheel axis is smaller than 32.37 cm and the weight point is stabil at (-13.22 cm ; 14.37 cm) based on the reference point. Moreover%2C it has a feature than can decrease wheelbarrow speed in descend way and decrease the effect of vibrations as well%2C the net weight is smaller than 21%2C6 kg and the support of wheelbarrow is lower than 32.5 cm. Abstract in Bahasa Indonesia : Wheelbarrow merupakan salah satu alat manual material handling yang banyak digunakan masyarakat. Oleh karena itu perlu dilakukan penentuan karakterisik wheelbarrow yang baik yang telah memper¬timbangkan faktor yang paling mempengaruhi konsumsi energi dan kemungkinan cedera untuk mengetahui prioritas perbaikan. Eksperimen dilakukan dengan menggunakan metode Taguchi. Dari analisis posisi tubuh diketahui bahwa posisi tubuh paling baik saat pengangkatan adalah posisi tubuh lurus dengan lengan sejajar tulang belakang. Berdasarkan kuesioner diketahui bahwa keluhan terbanyak responden adalah pada telapak tangan%2C lengan%2C bahu%2C siku dan pergelangan tangan. Berdasarkan informasi-informasi tersebut maka dapat disimpulkan bahwa wheelbarrow yang baik adalah wheelbarrow mempunyai jarak antara tumpuan manusia dengan poros roda yang lebih panjang dari 110 cm%2C mempunyai jarak horizontal titik berat beban terhadap poros yang lebih kecil dari 26%2C53 cm%2C mempunyai jarak vertikal titik berat beban terhadap poros yang lebih kecil dari 32%2C37 cm%2C mempunyai titik berat beban yang stabil (tetap pada (-13%2C22 cm ; 14%2C37 cm) terhadap titik acuan)%2C mempunyai fitur yang dapat mengurangi kecepatan wheelbarrow di jalan menurun%2C mempunyai fitur yang dapat meredam getaran%2C mempunyai berat bersih wheelbarrow yang lebih ringan dari 21%2C6 kg%2C mempunyai tinggi kaki penyangga yang lebih rendah dari 32%2C5 cm. wheelbarrow%2C energy expenditure%2C risk of injuries%2C taguchi methods.